Micro-scale distribution of algae in a Pyrenean peat-bog, Spain - Cambra, Jaume (HIDROBIOLÓGICA, 2016)
We studied the small-scale distribution of algae in the Bassa Nera peat-bog (Pyrenees, NE Spain). A total of 110 algal taxa were identified, some of which are rarely recorded in Spain: Cystodinium cornifax, Euastrum insigne and Desmidium swartzii. Three algal assemblages were distinguished along the studied gradient. Data on the flora and structure of the algal communities, as well on conservation interest are given.